(untitled) (Research, Society and Development, 2021)
Bibliometric analysis seeks to evaluate scientific productions, enabling the compilation of various types of information such as effective publications, authors and shows the direction of future productions. Biochar is the name given to biomass of plant origin that has undergone a burning process. The biochar has gained prominence in recent years for its versatile material. Rich in carbon and used for carbon sequestration, nutrient retention, it improves soil fertility, the physical and biological properties of the soil and increases agricultural yield. It is a promising adsorbent for the remediation of organic and inorganic contaminants from soil and water. This study aims to analyse qualitatively and quantitatively, using bibliometric methods, the publications of research articles related to the use of biochar as an adsorbent, in the period 2011-2021. The base data for this research were collected in October 2020, in the Scopus database. The selected articles were analysed with the aid of VOsviewer®. There was an advance in studies on biochar in the period. The largest number of articles cited and the highest productivity are Chinese. The predominant language is English and the predominant area is environmental sciences.